Entre a intenção e o ato: uma análise da política de contratualização dos hospitais de ensino (2004-2010) - Chioro, Arthur [UNIFESP] (2011)
Introduction: The Teaching Hospital Restructuring Program, comprising hospital-related certification and configuration of agreements, was introduced in 2004 by the Brazilian Government. It is one of the strategies to handle the crisis in this sector as it brings forth new funding, management and relationship standards between teaching hospitals and the health system by executing agreements with the local manager of the Brazilian National Health Care System (Sistema Único de Saúde – SUS). Methodology: the research was carried out in four hospitals belonging to the first group to enter into an agreement in 2004 under different legal regimes and selected through a drawing process. The initial motivation was to analyze possible changes found in the daily life of the teaching hospitals deriving from such government policy, in an attempt to characterize the role played by different institutional actors towards this policy, in addition to managers’ protagonism and the difficulties found in its implementation. Therefore, documents were analyzed and 32 interviews were performed with hospital managers, SUS managers, and managers from the federal ministries responsible for the formulation and performance of the contracting policy. Implication Analysis: The author’s implication with the object of study is openly dealt with as the research is conducted (The author coordinated policy formulation and initial implementation). The main methodological challenge was getting through an “epistemological displacement” from the governmental position occupied by the subject in the past to the actual position of an epistemic subject in order to explicitly deal with such “contamination-relationship” and try to construct “alterity relationships” that might lead to understanding the configuration of agreements as viewed by the actors who were responsible for its effective implementation. Data Analysis: starting from the construction of empirical mirror-categories (as they merely “reflect” elements contained in the policy evaluation grid) and novelty-categories (encompassing unpredictable aspects in the original policy formulation), equations were thought of for each hospital. These equations always comprised the same categories, though denoting the different intensities that they would gradually present, as well as different connecting forces between them. The analysis was accomplished within three different analytical plans. The first contains a characterization of changes occurred as the configuration of agreements began. The political guidelines regarding assistance, management, education in health, technological evaluation and incorporation were taken as a point of reference. The second plan analyzes the bets that were implicit placed during the formulation of the configuration of agreements, when indications about its non-explicit theoretical-conceptual bases were pursued. Now, on a deeper abstractional level, the third plan develops a theoretical reflection on the theme of reason and rationality in modern times, in an attempt to find connections with the instrumental rationality found in the hegemonic structural-functionalist paradigm of organizational studies and interventions and, as pointed by the study, in the formulation of the teaching hospital agreement configuration policy itself. Results: In the first analytical plan, the most visible progress made by the configuration of agreements was the change in the funding profile, resulting in financial as well as economic balance and the fight against indebtedness, although with diverse intensities and reflections for the hospitals under study. However, guidelines for teaching, permanent education, technological incorporation and research, which were fundamental for the production of a new teaching hospital, stood for clearly “forgotten” purposes as the policy was introduced. In addition, it was not capable of providing considerable changes in relation to management and health care qualification. A second analytical plan provides the analysis of the implicit political bets and their different accomplishment rates. The expectation of inducing a new management rationality from a government policy was not fulfilled as the complexity of the teaching hospital micropolitics was underestimated. The idealized participation arrangements that were strongly inspired in the production of actors – who emphasized the need to “constitute collective subjects” through the horizontalization and democratization of relationships among workers, users and managers – are faced with operational difficulties so they do not produce a new management logic for the teaching hospitals. Therefore, the contracting policy ends up reproducing the usual conservative behavior found in public management – a specific, instrumental rationality that emphasizes administrative action and excessive standardization. The third analytical plan promotes a theoretical discussion about the concept of reason in modern times, particularly about what has been called, since Max Weber, as the “increasing rationalization of society”. It is within such a theoretical-conceptual frame that intelligibility towards the so-called increasing rationalization of medical-hospital practices is searched for. This is characterized by the ideal operation of hospitals known as "scientific", efficient, predictable, and parameterized by the market and its criteria of competition and survival. This new “rationalized hospital” presents the “dream hospital" of all interviewed managers, either in public or private sectors, as they surprisingly identified it as being the hospital desired by the contracting policy! All that points to the complexity that is inherent to the formulation of governmental policies, mainly the moment of their implementation by actors in their real acting conditions. Studies and interventions are therefore critical to dispute other senses for hospital management. These should not be the ones as shaped by instrumental rationality, which goes on establishing a unique and triumphant possible rationality, bringing forth the theoretical as well as political fight against the extreme functionalization and homogenization of the ways to promote management and its unique truth. Back to the Start: the study is concluded through reflections presented by the author, who was faced into a new displacement at the end of the research, due to political as well as professional reasons, this time as a local SUS manager, as he became responsible for the introduction – in act – of a configuration of agreements policy in local teaching hospitals.